Idiopathic Generalized Epilepsy with Hemiconvulsions - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
Three adolescent patients with hemiconvulsive seizures and 3-cps generalized spike-and-wave discharges on EEG are reported from the National Hospital, Queen Square, London, UK.